Application of Near‐IR Absorption Porphyrin Dyes Derived from Click Chemistry as Third‐Order Nonlinear Optical Materials. Issue 1 (16th October 2015) - Mi, Yongsheng; Liang, Pengxia; Yang, Zhou; Wang, Dong; Cao, Hui; He, Wanli; Yang, Huai; Yu, Lian
Abstract: Recently, third‐order nonlinear properties of porphyrins and porphyrin polymers and coordination compounds have been extensively studied in relation to their use in photomedicine and molecular photonics. A new functionalized porphyrin dye containing electron‐rich alkynes was synthesized and further modified by formal [2+2] click reactions with click reagents tetracyanoethylene (TCNE) and 7, 7, 8, 8‐tetracyanoquinodimethane (TCNQ). The photophysical properties of these porphyrin dyes, as well as the click reaction, were studied by UV/Vis spectroscopy. In particular, third‐order nonlinear optical properties of the dyes, which showed typicalD ‐π‐A structures, were characterized by Z‐scan techniques. In addition, the self‐assembly properties were investigated through the phase‐exchange method, and highly organized morphologies were observed by scanning electron microscopy (SEM). The effects of the click post‐functionalization on the properties of the porphyrins were studied, and these functionalized porphyrin dyes represent an interesting set of candidates for optoelectronic device components. Abstract : Let′s get photophysical ! A new functionalized porphyrin dye containing electron‐rich alkynes was synthesized and further modified by formal [2+2] click reactions with tetracyanoethylene and 7, 7, 8, 8‐tetracyanoquinodimethane. Their photophysical properties, as well as third‐order nonlinear optical properties, which showed typicalD ‐π‐A structures, were characterized. Selfassembly properties were investigated, and highly organized morphologies were also observed by SEM.